TEACHING ENTREPRENEURSHIP THROUGH A CLIL APPROACH IN RUSSIAN TECHNICAL UNIVERSITIES - Lopukhova, Yulia; Makeeva, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In recent decades, increasing numbers of EMI (English as Medium of Instructions) courses have been added to university course offerings in countries where English is not the first language, as a way of supporting university internalization and addressing the global status of English. However, some studies argue that EMI courses might affect the overall learning of course content because of students' poor lecture comprehension and passive engagement in class. In order to facilitate student engagement and improve learning experiences in EMI courses, the authors introduce a CLIL approach that would facilitate students' overall learning in entrepreneurship. By focusing rather on the content, students acquire the target language unconsciously. Learning a language through content does not only increase the students’ motivation but it also improves the students’ performances, both in language and content. This article demonstrates the possibility of combining the subject Entrepreneurial Leadership and CIL, and it intends to explore possible benefits and obstructions. During the research it became evident that the students’ interest in Entrepreneurial Leadership which was realized in the frame of Masters’ Programme “Entrepreneurs for Tomorrow” as well as their concentration increased, mainly due to the use of different teaching techniques employed and partly due to use of English as the language of instruction. Further issues raised in the field of CLIL Entrepreneurial Leadership will be discussed in the empirical part and in the curriculum analysis.